2000
DOI: 10.1094/cchem.2000.77.4.484
|View full text |Cite
|
Sign up to set email alerts
|

Moisture Redistribution and Phase Transitions During Bread Staling

Abstract: Cereal Chem. 77(4):484-488Standard white breads were stored with or without crust at 25°C in hermetic pouches. During two weeks of storage, the crumb moisture content and water activity (a w ) decreased significantly when stored with crust. When stored without crust, moisture content and a w remained relatively unchanged. The causes of the initial firming of both breads over zero to seven days were not conclusive. But when stored beyond seven days, bread stored with crust was significantly firmer in texture an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
106
2
4

Year Published

2005
2005
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 193 publications
(122 citation statements)
references
References 10 publications
10
106
2
4
Order By: Relevance
“…This result is in agreement with Ribotta and Bail (2007), who found reduction in crumb moisture and an increment in the crust moisture during the storage days. Baik and Chinachoti (2000) reported that bread crumb stored with crust showed reduction in moisture during the 2 weeks of storage at room temperature. Czuchajowska and Pomeranz (1989) reported that the crumb moisture decreases from approximately 450 to 435 g/kg during storage.…”
Section: Moisture Content Analysismentioning
confidence: 99%
See 3 more Smart Citations
“…This result is in agreement with Ribotta and Bail (2007), who found reduction in crumb moisture and an increment in the crust moisture during the storage days. Baik and Chinachoti (2000) reported that bread crumb stored with crust showed reduction in moisture during the 2 weeks of storage at room temperature. Czuchajowska and Pomeranz (1989) reported that the crumb moisture decreases from approximately 450 to 435 g/kg during storage.…”
Section: Moisture Content Analysismentioning
confidence: 99%
“…The gelatinization enthalpy change temperature is correlated to the retrogradation of amylopectin, which occurred during storage time (Baik & Chinachoti, 2000). The ΔH value indicated recrystallization of amylopectin with time (Baik & Chinachoti, 2000).…”
Section: Bread Crumb Thermal Propertiesmentioning
confidence: 99%
See 2 more Smart Citations
“…In fact, 0by maintaining bread in a proper packaging the loss of water is lowered, but staling still occurs, because of the migration of water from crumb to crust. 2,3 Another factor contributing to the staling process is the progressive increasing of interactions (cross-binding) between the proteic fraction, in particular the gluten, and residues of swollen starch granules. During ageing these interactions increase in number and strength, intensifying the perceived firmness.…”
Section: Introductionmentioning
confidence: 99%